Predictors of iron overload toxicity in multi-transfused beta-thalassemic children - Mishra, Nihar Ranjan; Biswal, Sumeet Soumyaranjan; Majhi, Subash Chandra (Indian Journal of Child Health, 2019)
Introduction: There are certain risk factors or predictors that can be used for early detection of cardiac iron overload to improve the long-term gains in beta-thalassemic children. Objective: The aim of the study was to consider the predictive abilities of some of the clinical attributes of the beta-thalassemia patients regarding cardiac iron overload to identify at risk patients. Materials and Methods: This current observational study was conducted in the Department of Pediatrics, VIMSAR, Burla from November 2016 to October 2018. A total of 105 thalassemic children were enrolled in the study after satisfying the inclusion criteria (multi-transfused beta-thalassemia children in the age group of 6–14 years). All the relevant data were collected and correlation-regression statistics were done using computer-based software. Results: Serum ferritin has weak negative correlation with left ventricular end diastolic diameter (LVEDD) (r=–0.511, p=0.000), good negative correlation with ejection fraction (EF) (r=–0.604, p=0.000), and weak positive correlation with left ventricular end systolic diameter (LVESD) (r=0.084, p=0.393). Number of units of packed red cell transfusion has strong negative correlation with EF (r=–0.785, p=0.000), weak negative correlation with LVEDD (r=–0.297, p=0.005), and weak positive correlation with LVESD (r=0.413, p=0.000). Corrected logistic regression equation, i.e., cardiac iron overload=1.997 (age in years) –3.119 (gender) –0.078 (units of packed red blood cells [PRBC]) +0.003 (serum ferritin in ng/ml) –0.149 (LVEDD in mm) –0.235 (weight in kg) –10.928 with prediction of 94.3%. Conclusions: Age of the patient, serum ferritin level, and number of units of PRBCs transfused, LVEDD and weight of the child are good predictors of myocardial iron overload among childhood beta-thalassemic and hence can be used as indices for monitoring of onset of cardiac iron overload.